Risk Factors for Mortality From Late-Onset Sepsis Among Preterm Very-Low-Birthweight Infants: A Single-Center Cohort Study From Singapore - Goh, Guan Lin; Lim, Charis Shu En; Sultana, Rehena; De La Puerta, Rowena; Rajadurai, Victor Samuel; Yeo, Kee Thai (Frontiers in Pediatrics, 2022)
Objective: To determine the risk factors for mortality associated with late onset sepsis (LOS) among preterm very-low-birthweight (VLBW) infants. Study Design: We performed a retrospective cohort study of infants born <32 weeks gestation and <1500gm admitted to a Singaporean tertiary-level neonatal intensive care unit. We determined the clinical, microbial and laboratory risk factors associated with mortality due to culture-positive LOS in this cohort. Results: A total of 1740 infants were admitted, of which 169 (9.7%) developed LOS and 27 (16%) died. Compared to survivors, those who died had lower birth gestational age (median 24 vs 25 weeks, p=0.02) and earlier LOS occurrence (median 10 vs 17 days, p=0.007). There was no difference in the incidence of meningitis (11.1% vs 16.9%, p=0.3), NEC (18.5% vs 14.8%, p=0.6) or intestinal surgery (18.5% v 23.3%, p=0.6) among infants who died compared to survivors. Gram-negative bacteria accounted for 21/27 (77.8%) LOS-associated deaths and almost all (13/14, 93%) fulminant episodes. Presence of multiorgan failure, as evidenced by need for mechanical ventilation (100% vs 79.0%, p=0.008), elevated lactate (12.4mmol/L vs 2.1mmol/L, p<0.001) and inotropic support (92.6% vs 37.5%, p<0.001), was significantly associated with mortality. Infants who died had significantly lower white blood cell (WBC) counts (median 4.2x109/L vs 9.9x109/L, p=0.001), lower platelet count (median 40x109/L vs 62x109/L, p=0.01), and higher immature to total neutrophil (I:T) ratio (0.2 vs 0.1, p=0.002). Inotrope requirement [AOR 22.4 (95%CI 2.9, 103.7)], WBC<4x109/L [AOR 4.7 (1.7, 13.2)] and I:T ratio>0.3 [AOR 3.6 (1.3, 9.7)] were independently associated with LOS mortality. Conclusions: In a setting with predominantly Gram-negative bacterial infections, the need for inotropic support, leukopenia and elevated I:T ratio were significantly associated with LOS mortality among preterm VLBW infants.